GBG-banded ideogram of the European eel Anguilla anguilla L. (Osteichthyes, Anguilliformes) - SALVADORI, SUSANNA; COLUCCIA, ELISABETTA; CANNAS, RITA; CAU A; DEIANA AM (Cytogenetic and Genome Research, 2004)
GBG-banded ideogram of the European eel Anguilla anguilla L. (Osteichthyes, Anguilliformes) Salvadori S., Coluccia E., Cannas R., Cau A., Deiana AM Dipartimento di Biologia Animale ed Ecologia, Università di Cagliair (Italia) Increasing importance of acquaculture explains the development of studies on the reproduction, genetics and cytogenetics of fish domesticated species. While for man and many domisticated mammals, an International Siystem for Chromosome Nomenclature is available, it has yet to be estabilished for fishes because reproducible euchromatic G- and fluorochrome-banding patterns are difficult to obtain. The European el Anguilla anguilla is commercially important but since 1980’s, recruitments and catches have declined dramatically. Reports of A. anguilla karyotype using different banding techniques are numerous, but since chromosome classification criteria vary with authors, data comparison is difficult. Since the 1990’s, we have analyzed the kariotype of Atlantic ells A. anguilla european and A. rostrata (American). Here, we present the GBG-banded ideograms of A. anguilla chromosomes. Applying the Cromowin karyotyping system (Amplimedical S.p.A.), we analyzed GBG-banded chromosomes obtained by early BrdU incorporation in lymphocyte cultures and FPG staining of chromosome spread, and constructed diagrammatic representation. Our goal is to estabilish an eel standard karyotype, which agrees with all A. anguilla karyotes previously reported. Moreover, this A. anguilla standard karyotype will serve as a landmark for studies on other eel species. In particular, comparison with the karyotype of the other Atlantic species A. rostrata will allow us to point out interspecific homeologies as well as rearrangements involved in karyoype evoluion of these species.